Potential of long non‐coding RNAs in cancer patients: From biomarkers to therapeutic targets - Chandra Gupta, Subash; Nandan Tripathi, Yashoda (International journal of cancer, 2017)
Because of high specificity and easy detection in the tissues, serum, plasma, urine and saliva, interest in exploring the potential of long non‐coding RNAs (lncRNAs) in cancer patients continues to increase. LncRNAs have shown potential as a biomarker in the diagnosis and prognosis of bladder cancer, prostate cancer, gastric cancer, pancreatic cancer, breast cancer and many other cancer types. Some lncRNAs have also been used as adjunct to improve the specificity and sensitivity of existing biomarkers. The molecular tools such as RNA‐seq, RNA‐FISH, ic‐SHAPE and quantitative real‐time PCR have been used for examining the lncRNAs' potential. Some lncRNAs such as PCA3 is now routinely used in the clinic for the diagnosis of prostate cancer. Single nucleotide polymorphisms (SNPs) in lncRNAs can also be used as a predictor of cancer risk. Although ongoing studies continue to unravel the underlying mechanism, some lncRNAs have been used as therapeutic targets for the selective killing of cancer cells in patients. Thus lncRNAs are emerging as convenient and minimally invasive diagnostic/prognostic markers, and also as therapeutic target. Companies such as the Curna Inc., MiNA Therapeutics Ltd. and RaNA Therapeutics Inc. have been taking steps to develop lncRNA based strategies against cancer. In this review, we discuss the potential of lncRNAs as biomarkers and therapeutic targets in cancer patients.